Epidemiology and morbidity of spina bifida in Hispanic Americans: a systematic review - Roxanna M Garcia; Sandi K Lam; Sunny Abdelmageed; Megan Votoupal (BMJ Publishing Group, 2024)
Objective To comprehensively describe the epidemiology and morbidity of spina bifida in Hispanic Americans and identify risk factors associated with the increased prevalence of spina bifida.Design A systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Data sources Three databases (MEDLINE, Embase and Scopus) were searched between inception of the database and June 2023. Study designs included case-control, descriptive, cross-sectional and databases.Eligibility criteria Observational and experimental analytical studies reporting epidemiology or morbidity of spina bifida in Hispanic Americans or Latinx individuals were eligible.Data extraction and synthesis Data were extracted independently by authors. Descriptive analysis was used to summarise findings.Results Of 392 publications, 32 studies met inclusion criteria. Study periods ranged from 1955 to 2020. A total of 50 382 patients with spina bifida were included and 13 209 identified as Hispanic American (26.2%). Five studies report higher prevalence of spina bifida at birth per 10 000 births in Hispanic Americans compared with non-Hispanic white individuals, while one reported no significant difference (2.11 vs 2.24). Risk factors associated with spina bifida included prenatal exposures, sociodemographic factors and maternal clinical characteristics. Lower levels of maternal education, age and income were associated with an increased risk of spina bifida. Eleven papers found spina bifida had high morbidity among Hispanic Americans resulting in high financial, physical and socioeconomic impacts. There was high study heterogeneity that can be explained by the varying time periods and geographical distribution.Conclusion Increased prevalence and morbidity of spina bifida in Hispanic Americans are due to a variety of inter-related factors relating to existing health disparities. High heterogeneity across the studies suggests a need for future studies and increased standardisation of reporting guidelines.